The Role of Single Parents in Developing Independence in Early Childhood - Arsanti, Alya; Nurzannah, Nurzannah (UPI Kampus Cibiru, 2024)
There are many children in society who are educated by single parents. Likewise, several children at RA Tarbiyah Isamiyah Al-Musthafawiyah. His parents experienced several obstacles in raising their children, because they had to work to earn a living while simultaneously educating and raising their children. This causes obstacles for single parents in developing their children's character, especially regarding independence. The aim of this research is to describe the role of single parents in developing independence in early childhood. The research sample was determined using a purposive sampling technique with the criteria being single parents who had children aged 4-6 years. This research is a qualitative descriptive study. The collection techniques used were interviews and observation. The research results show that the role of single parents in developing children's independence is very large by being a motivator, facilitator and role model for children who also wake up early. Based on the research results, it can be concluded that parents play a very important role in training their children to be independent by habituating and controlling their children's daily activities. This research can provide an understanding to parents of the importance of the role of education and motivation in children through small things in the home environment such as giving examples of getting up early, making beds, then bathing. So that children grow to be more independent.